The emergence of aesthetic medicine market in Russia - S. N. Svanadze; G. P. Skvirskaya (Сеченовский вестник, 2016)
The article discusses the marketing research and emergence aesthetic medicine market in Russia after the recent official recognition of Plastic Surgery specialty. One of the most popular aesthetic procedures is the mammoplasty. At the moment, this market is actively developing, reflecting the changes in patients’ demand and the optimization of the healthcare management. The article dwells upon the challenges of the private aesthetic surgery business and the ways to overcome them.